Analysis of syphilis incidence in the Republic of Mordovia - Ekaterina V. Blinova; Oksana P. Balykova; Denis I. Laseev; Natalya N. Chernova; Ludmila I. Kitaeva (Наука и инновации в медицине, 2019)
Objectives to study the syphilis morbidity rate in the population of the Republic of Mordovia in years 20152017, to determine the age, sex and social patterns of morbidity.